2016
DOI: 10.1111/cas.12984
|View full text |Cite
|
Sign up to set email alerts
|

Tuberin regulates reactive oxygen species in renal proximal cells, kidney from rodents, and kidney from patients with tuberous sclerosis complex

Abstract: Reactive oxygen species (ROS) are an important endogenous source of DNA damage and oxidative stress in all cell types. Deficiency in tuberin resulted in increased oxidative DNA damage in renal cells. In this study, the role of tuberin in the regulating of ROS and NADPH oxidases was investigated. Formation of ROS and activity of NADPH oxidases were significantly higher in mouse embryonic fibroblasts and in primary culture of rat renal proximal tubular epithelial tuberin‐deficient cells compared to wild‐type cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…To evaluate the source of ROS in heptachlortreated HK-2 cells, we measured the NOX-4 activity which seems to be primary renal oxidase and has been identified as a source for ROS in renal cells. 26 Our results revealed significant increased activity of NOX-4 in a dose-dependent manner in a heptachlorstimulated HK-2 cells ( Figure 5). Earlier, similar studies also reported that OCPs induced NOX activation in different cell line models.…”
Section: Discussionmentioning
confidence: 51%
“…To evaluate the source of ROS in heptachlortreated HK-2 cells, we measured the NOX-4 activity which seems to be primary renal oxidase and has been identified as a source for ROS in renal cells. 26 Our results revealed significant increased activity of NOX-4 in a dose-dependent manner in a heptachlorstimulated HK-2 cells ( Figure 5). Earlier, similar studies also reported that OCPs induced NOX activation in different cell line models.…”
Section: Discussionmentioning
confidence: 51%
“…Nox2 is the major Nox isoform responsible for macrophages activation [ 22 ]. Nox2 is expressed also in kidney tissues [ 23 , 24 ] and tubular epithelial cells [ 25 ]. Therefore, targeting all Nox isoforms might be a better strategy against ROS-induced kidney injury in diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress is usually produced by reactive oxygen species (ROS). Oxidative stress is common in CKD and serves an important role in renal fibrosis progression ( 5 ). ROS attack, denature and modify the structure and function of molecules and activate redox-sensitive transcription factors and signaling pathways, resulting in tissue injury and dysfunction.…”
Section: Relationship Between Ers and Oxidative Stressmentioning
confidence: 99%
“…ROS attack, denature and modify the structure and function of molecules and activate redox-sensitive transcription factors and signaling pathways, resulting in tissue injury and dysfunction. These events increase ECM expression and promote the development of renal fibrosis ( 5 ).…”
Section: Relationship Between Ers and Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation